An enhancement of Boolean retrieval systems based on term co-occurrence frequencies / Un amélioration des systèmes d’information basé sur la cooccurrence de termes - Wong, S.K.M.; Ziarko, W.; Raghavan, V.V. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
see pdf